1995
DOI: 10.1083/jcb.128.5.863
|View full text |Cite
|
Sign up to set email alerts
|

The Cdc31p-binding protein Kar1p is a component of the half bridge of the yeast spindle pole body.

Abstract: Abstract. KARl has been identified as an essential gene which is involved in karyogamy of mating yeast cells and in spindle pole body duplication of mitotic ceils (Rose, M. D

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
188
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(193 citation statements)
references
References 37 publications
(102 reference statements)
4
188
1
Order By: Relevance
“…Although a recent study showed Ca 2ϩ -independent binding of centrin to a target protein (50), in most cases the activation of centrins by Ca 2ϩ is necessary for the interaction with their binding partners (16,18). In the yeast Saccharomyces cerevisiae, Ca 2ϩ facilitates binding of Cdc31p, the yeast centrin homologue, and of the human centrin isoforms 1 and 2 to Kar1p, which is necessary for division of the yeast cell (48,51,52). In our previous centrin blot overlay assays, the binding of recombinant MmCen1 to all detected interacting proteins was Ca 2ϩ -dependent (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent study showed Ca 2ϩ -independent binding of centrin to a target protein (50), in most cases the activation of centrins by Ca 2ϩ is necessary for the interaction with their binding partners (16,18). In the yeast Saccharomyces cerevisiae, Ca 2ϩ facilitates binding of Cdc31p, the yeast centrin homologue, and of the human centrin isoforms 1 and 2 to Kar1p, which is necessary for division of the yeast cell (48,51,52). In our previous centrin blot overlay assays, the binding of recombinant MmCen1 to all detected interacting proteins was Ca 2ϩ -dependent (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The representation of Spc29 in between Spc110 and Spc42 is highly schematic, as the exact nature of its function as part of the Spc110 complex remains to be established. Cdc31, Kar1, Mps3, and Sfi1 (Baum et al 1986;Rose and Fink 1987;Spang et al 1993Spang et al , 1995Biggins and Rose 1994;Jaspersen et al 2002;Kilmartin 2003;Li et al 2006). Kar1 and the SUN domain protein Mps3 each contain a single membrane-spanning domain (Rose and Fink 1987;Jaspersen et al 2002).…”
Section: Structure and Duplication Cycle Of Yeast Spbsmentioning
confidence: 99%
“…The SPB is a proteinaceous structure that is embedded in the nuclear envelope, and its duplication marks exit from the G 1 phase and the onset of chromosome duplication. The composition of the SPB has been defined, and the steps that lead to its duplication have been studied extensively using biochemical, genetic, and microscopic methods (3,5,6,18,24,28,30,43,44). An important component of the SPB is Cdc31 (3, 13), which in yeast is encoded by the essential CDC31 gene.…”
mentioning
confidence: 99%